Norms Across Cultures: A Cross-Cultural Meta-Analysis of Norms Effects in the Theory of Planned Behavior. (November 2019) - Fischer, Ronald; Karl, Johannes Alfons; Fischer, Moritz Valentin
Norms have emerged as a central concept across various fields of psychology. In social psychology, norms have been important to predict intentions and behavior in social psychology, but cultural variability has not been examined. In cultural psychology, norms have also played a central role in explained cultural differences. In contrast, to date, variability in norm-intention and norm-behavior relationships has not been systematically investigated. Any systematic variability may be challenging to both social and cultural psychology. We reanalyzed effect sizes taken from five previously published meta-analyses and demonstrate that the relative strength of norm-intention and norm-behavior correlations are systematically higher in contexts in which individuals are more flexible and pay more attention to situational variables as well as in less economically developed societies. We also found significant, but weaker, effects for individualism and tightness–looseness. Meanwhile, behavior domain effects also emerged, which suggests that norms are behavior specific. Norms effects systematically vary across modern societies, but more attention is needed to investigate culturally conditioned domain and behavior effects thoroughly.